Occupant behavior model and its involvement in building optimization design: a review - Wang Guyixin; Pengcheng Zhu; Sheng Yao; Jingyu Yuan; Tianhua Hu (Journal of Asian Architecture and Building Engineering)
The occupant behavior has a significant impact on the building performance. This review offers researchers and practitioners a clear understanding of the evolution of the occupant behavior model and its involvement in building optimization design, providing guidance for future research. Studies are selected if they are peer-reviewed conference proceedings and journal papers published from 2005 to 2023. By analyzing 203 core papers from the Web of Science, a bibliometric study is conducted using CiteSpace. The findings indicate that research on occupant behavior has advanced significantly since 2005, with China being the most active country. The interaction between occupant and building performance, development of occupant behavior model, building optimization framework, and optimized strategies in buildings are the four fundamental topics. Finally, the current challenges and future opportunities are discussed. Future research should focus on conducting real-case quantitative studies, expanding performance simulation, developing comprehensive techniques, improving user-system interaction, and exploring feasible social practices. However, limitations arise due to deficiencies in the thoroughness and depth of analyses resulting from sample constraints. To obtain more reliable results, a broader and more systematic approach to collecting publications is needed.